Of devotion and death - Hastings, Anastasia (A dear Miss Hermione mystery, 2026)
Violet Manville knows everything about manners--and murder. Violet is looking forward to taking some time away from the advice column she writes under the nom de plume Miss Hermione. She can't wait to head off to Venice to spend some time with Eli Marsh, a mysterious, annoying, and extremely attractive American. Little does she suspect that the specter of death will come calling at her front door in the person of Ash Kumar, a man she once knew--and loved--when she lived in India. She certainly doesn't expect Ash to be arrested for his wife's murder on her front door step. As Violet tries to unravel the murder, she is pulled between between the two men. As the past and present become blurred, she soon discovers that the truth can be deadly.